Bioinspired capillary transistors - Liu, Xiaojiang (2024)
Inspired by the unidirectional liquid spreading on Nepenthes peristome, Araucaria leaf, butterfly wings, etc., various microfluidic devices have been developed for water collection, irrigation, physical/chemical reaction, and oil-water separation. Despite extensive progress, most natural and artificial structures fail to enhance the Laplace pressure difference or capillary force, thus suffering from a low unidirectional capillary height (<30 mm). In this work, asymmetric re-entrant structures with long overhangs and connected forward/lateral microchannels are fabricated by 3D printing, resulting in a significantly increased unidirectional capillary height of 102.3 mm for water, which approximately corresponds to the theoretical limit. The overhangs can partially overlap the forward microchannels of the front structures without direct contact, thus enhancing the Laplace pressure difference and capillary force simultaneously. Based on asymmetric and symmetric re-entrant structures, capillary transistors are proposed and realized to programmably adjust the capillary direction, height, and width, which are envisioned to function as switches/valves and amplifiers/attenuators for highly efficient liquid patterning, desalination, and biochemical microreaction in 3D space.